(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article analyzes the adulthood period as a key stage in human development that affects psychological well-being. The research covers the theoretical and methodological foundations of the concept of psychological well-being based on the views of leading psychologists such as Carol Ryff, M. Seligman, and E. Diener, as well as approaches from representatives of the Uzbek psychological school. Internal (cognitive-emotional) and external (socio-cultural, professional) factors affecting psychological well-being during adulthood are systematically examined. The article identifies the mechanisms for developing well-being based on the analysis of empirical research and develops scientific and practical recommendations for supporting psychological stability during this period.